Dampak Program Usaha Agribisnis Perdesaan (PUAP) Terhadap Tingkat Pendapatan Petani (Studi Kasus Pada Gabungan Kelompok Tani (GAPOKTAN) Bina Sejati Di Desa Tebing Tinggi Pangkatan Kecamatan Pangkatan) - Riski Nuria Tambunan; Yudi Triyanto; Siti Hartati Yusida Saragih (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2020)
The Impact of the Rural Agribusiness Business Program (PUAP) on the level of income of farmers that aims to: (1) To determine the level of success of the implementation of the PUAP program in Tebing Tinggi Pangkat Village. (2) To find out the constraints and obstacles faced in the implementation of the PUAP program (3) To find out the amount of PUAP farmers 'income compared to the farmers' income before participating in PUAP. Samples were taken as many as 113 random farmers. This research was conducted at Gapoktan including descriptive-quantitative research types. The type of data used is quantitative data. The research subject is Gapoktan who receives PUAP funds, and the object is Gapoktan income PUAP fund recipients. The data used is quantitative data in the form of income data for Gapoktan members who receive PUAP funds. The analysis technique used is descriptive statistical analysis, namely paired sample t-test. The results showed that: (1) there was a difference in the level of Gapoktan farm income after following the PUAP program. The income earned by PUAP farmers (Rp. 1,558.23 / month) is significantly higher, compared to the income before joining PUAP (Rp. 815.58 / month). (2) the level of success of the PUAP program in the Gapoktan Bina Sejati KelurahanTebing Tinggi Pangkatans is very high. From various Impacts, PUAP Program, and Farmer Income are almost all achieved. The success has been distributed to the PUAP BLM funds to all agribusiness farmers who apply for credit. Funds have been received quickly, precisely, without any deductions (3) In the implementation of the PUAP program in Gapoktan Bina Sejati KelurahanTing Tinggi Pangkat, no significant obstacles were found. Keywords: PUAP Program, PUAP Fund, Income Level, Gapoktan